2021
DOI: 10.1002/prot.26210
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization underlies the aggregation propensity of intrinsically disordered coiled‐coil domain‐containing 124

Abstract: Coiled‐coil domain‐containing 124 (CCDC124) is a recently discovered ribosome‐binding protein conserved in eukaryotes. CCDC124 has regulatory functions on the mediation of reversible ribosomal hibernation and translational recovery by direct attachment to large subunit ribosomal protein uL5, 25S rRNA backbone, and tRNA‐binding P/A‐site major groove. Moreover, it independently mediates cell division and cellular stress response by facilitating cytokinetic abscission and disulfide stress‐dependent transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…6A-B). This could also be due to the effect of GFP11-tag on the proper dimerization/oligomerization dynamics of CCDC124 protein [17,23]. Nevertheless, results presented in this work indicated that as suggested by the previously established interactome of CCDC124 [17], under certain cellular circumstances CCDC124 localizes to G3BP1-positive SGs in a context dependent manner [24].…”
Section: Discussionmentioning
confidence: 54%
“…6A-B). This could also be due to the effect of GFP11-tag on the proper dimerization/oligomerization dynamics of CCDC124 protein [17,23]. Nevertheless, results presented in this work indicated that as suggested by the previously established interactome of CCDC124 [17], under certain cellular circumstances CCDC124 localizes to G3BP1-positive SGs in a context dependent manner [24].…”
Section: Discussionmentioning
confidence: 54%